Main Factors in the Development of Tourism.Touristic Resources of Uzbekistan (Texas Journal of Philology, Culture and History, 2022)
This article talks about the main factors in the development of tourism, the fact that tourism is a highly profitable industry for the country, and the specific features of management in the field of tourism.